Social and individual risk factors for suicide ideation among Chinese children and adolescents: A multilevel analysis. (18th April 2016) - Tan, Ling; Xia, Tiansheng; Reece, Christy
Abstract : The objective of this study was to investigate the prevalence and predictors of suicide ideation among primary, middle and high school students. We used multilevel modelling to investigate suicide ideation among 12, 733 Chinese children and adolescents aged 9–18 years from wide range of areas across China. Approximately, 32.09% of children and adolescents reported suicide ideation, with females were more likely to report suicide ideation than males (38.09% vs. 29.95%). Our results showed that the risk factors in primary school students were different from middle and high school student groups, whereas significant risk factors for middle and high school students were similar. The city's standard of living as indicated by the Engel coefficient and the city's divorce rate were positively associated with the prevalence of suicide ideation; in contrast, the school's pupil‐to‐teacher ratio was negatively correlated with elevated suicide ideation. Significant risk factors for suicide ideation included study anxiety, self‐accusation tendency, impulsive tendency, terror tendency and physical symptoms. These results have important implications for the prevention of suicide, suggesting that both contextual (city‐level) and compositional (individual‐level) factors could be important targets for prevention and intervention for children and adolescents at risk of suicide ideation.